Thermal Diffusivity of Frozen Soil. - Haynes,F D; Carbee,D L; VanPelt,D J (1980)
Knowledge of the thermal diffusivity of frozen soils is necessary for transient heat transfer analysis. The specific heat, thermal conductivity and density for a sand, a silt and a clay were obtained experimentally and used to calculate their thermal diffusivity. These properties were measured over a range of temperatures from -50 C to +45 C and for moisture contents from dry to saturated. The use of a differential scanning calorimeter for obtaining specific heat values was proven to be a reliable technique. (Author)